Covid Publics and Black Lives Matter: Posts Placards and Posters - Ruiz, Pollyanna (Javnost-The Public, 2022)
This article will examine the ways in which COVID has reconfigured the boundaries between online and offline, as well as public and private spaces. The threat posed by the global pandemic meant that public spaces quickly emptied, work zoomed into the home, and windows became notice boards filled with moraleboosting messages. Every Thursday, UK doorsteps became the space in which private individuals emerged from their own homes to express their gratitude to key workers in general and the NHS in particular. Whilst posters calling for better provision of PPE occasionally appeared in people’s windows, online talk about Booing for Boris never fully materialised into offline action, and the doorstep continued to function as the threshold between public and private space. However, the killing of George Floyd radically disrupted these threshold spaces. Information about Black Lives Matter demonstrations leapt from activists’ digital networks into the hyper-local and granular chains of communication established by COVID mutual aid groups, grassroots communities of care and small clusters of neighbours. Similarly, the slogans which had been circulating within activist networks for years quickly appeared on the placards of protesters as they moved through city spaces, before finally settling in people’s windows alongside rainbow posters urging neighbours to “stay safe.” When—on the first Thursday after the final NHS clap—many individuals chose to relinquish the comforting anonymity afforded by mass demonstrations and take the knee on their doorstep, they called their neighbours, as well as their government, into a dialogue about race. In this way, the windowpane and the doorstep finally became a dynamic space which both separated and connected online and offline as well as public and private spaces.